Peningkatan Literasi Kesehatan Reproduksi pada Anak Prasekolah melalui Intervensi Pendidikan Kesehatan - Helpa Devina Fitriansyah; Ellyda Rizki Wijhati (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Reproductive health is an aspect of health that should be introduced from childhood as part of efforts to improve and protect health. Introducing reproductive health to preschool children is an important step in promotion and prevention activities through teaching gender recognition, body parts, personal hygiene, physical privacy, and avoiding unsafe physical contact. This study aims to analyze the increase in reproductive health literacy in preschool children after a health education intervention. This type of research is quantitative with an experimental (pre-experimental) approach. The research design used is a pretest/posttest with one group (a single-group pretest/posttest design). The sampling technique used is total sampling with a sample size of 86 respondents. The data collection method is primary with a questionnaire measurement instrument. Data were collected using the non-parametric Wilcoxon test to assess the effect before and after the health education intervention. The results showed a significant increase in knowledge with a p-value of 0.000 (p < 0.05) after the intervention. Therefore, there was an increase in reproductive health literacy among preschool children after the intervention. Providing adequate reproductive health education from an early age helps increase children's protection from the risk of sexual violence, exploitation, and misunderstandings regarding bodily functions and sexuality. These findings suggest that reproductive health education can be a preventative and promotional measure starting from preschool age. It is recommended that reproductive health education be implemented sustainably, involving teachers, health workers, and parents.